2011
DOI: 10.5588/ijtld.10.0538
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in human immunodeficiency virus infected Ugandan children starting on antiretroviral therapy

Abstract: Objective To identify the incidence of tuberculosis (TB) in HIV-infected children in a resource-limited setting prior to and after antiretroviral therapy (ART) initiation. A secondary objective was to assess the impact of TB screening by Tuberculin skin testing (TST) and clinical history. Methods A retrospective cohort study of 1806 HIV-infected children and adolescents initiating ART from 2003 through July 1, 2006 in Kampala, Uganda. A TB screening program was instituted clinic-wide in January 2006. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 5 publications
7
29
0
Order By: Relevance
“…But this alone cannot explain our observed overall high prevalence, since a Ugandan study reported a lower prevalence compared to our study, 9.5%, although the majority of diagnoses (80%) were based on clinical features and chest radiograph, like in our study. 5 Nevertheless, our observed annual prevalence of co-infection was decreasing, with the rate in 2012 of 6.1% comparable to that of the Ugandan study (9.5%) reported in 2011. 5 The diagnosis of PTB in children remains challenging, partly due to the inability of children <8 years to generate a productive sputum specimen 17 and because of their paucibacillary nature.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…But this alone cannot explain our observed overall high prevalence, since a Ugandan study reported a lower prevalence compared to our study, 9.5%, although the majority of diagnoses (80%) were based on clinical features and chest radiograph, like in our study. 5 Nevertheless, our observed annual prevalence of co-infection was decreasing, with the rate in 2012 of 6.1% comparable to that of the Ugandan study (9.5%) reported in 2011. 5 The diagnosis of PTB in children remains challenging, partly due to the inability of children <8 years to generate a productive sputum specimen 17 and because of their paucibacillary nature.…”
Section: Discussionsupporting
confidence: 58%
“…5 Nevertheless, our observed annual prevalence of co-infection was decreasing, with the rate in 2012 of 6.1% comparable to that of the Ugandan study (9.5%) reported in 2011. 5 The diagnosis of PTB in children remains challenging, partly due to the inability of children <8 years to generate a productive sputum specimen 17 and because of their paucibacillary nature. 18 The majority (70%) of our study subjects were children <5 years of age.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations